Spectrophotometric Determination of Phosphates in Detergent Samples Available in Tansen, Palpa - Thapa, Yub Narayan; Khadka, Tribikram (Tribhuvan Journal, 2023)
Phosphate is primarily used as a builder in detergents, which helps soften hard water, thereby increasing the cleansing power of detergents. Extensive discharge of phosphate from detergents leads to eutrophication of surface water bodies. This work aims to assess the amount of phosphate present in detergent samples available in Tansen, Palpa, and compare its concentration between local and foreign detergents. Phosphate in detergent samples can be determined by the molybdenum blue phosphorus method using a spectrophotometer. The experimental process relies on forming a phosphomolybdate blue complex with ammonium molybdate and the subsequent reduction of the complex by hydrazine hydrate in an aqueous sulphuric acid medium. The system obeys Beer-Lambert’s law at 830 nm in the concentration range of 2-16 ppm. In this study, the phosphate concentration in local detergents (Dhoni, Light, V-Series, Nirma, Upahar, Patanjali, Rin Shakti and Dr Jhatka) varied from 15.54-33.03 ppm, and that of foreign detergents (Wheel, Super Check, Surf Excel, Tide and Ariel) ranged from 23.81- 32.65 ppm. The amount of phosphate was compared between local and foreign detergent samples using the student's t-test, which revealed no significant difference between them. The results obtained from the study disclosed that the detergents under investigation are within the permissible limits of phosphate. However, non- phosphate-based builders can be used to discourage the use of phosphate in detergents.